Black Lives Matter: Slavery Era and Contemporary Racial Experiences in African American Standup Humour - Adekunle, Idowu James (RIRAI Publisher, 2025)
Black Lives Matter is a significant contemporary issue, particularly in the United States. Its roots trace back to the era of slavery and continue into the present day. Black individuals have long faced systemic violence, sexual assault, racial killings, and various forms of discrimination that have historically marginalized them. These persistent struggles have contributed to the socioeconomic disenfranchisement of Black communities in the United States. The Black Lives Matter movement emerged as a response, advocating for the liberation of Black people from political, social, and economic oppression—both within the U.S. and globally. While previous studies have explored the movement through prose, poetry, drama, and journalism, few have examined its narratives through the lens of stand-up comedy. This study seeks to analyze how Black Lives Matter is represented in stand-up performances as a form of social commentary aimed at promoting the sociopolitical and economic emancipation of Black people in the United States. Recorded performances by African American comedian, Chris Rock, are examined. The analysis applies Schechner’s performance theory to uncover deeper meanings within the performances. Data were interpreted using both performance and literary analysis techniques.